Melodías para el tigre. Pablo de Rebullida y los indios de la Talamanca. 1694 - 1709 - Ruz, Mario Humberto (1991)
An analysis of the missionary work of Fray Pablo de Rebullida in Talamanca, Costa Rica, where entrusted with evangelization of the Indian. Includes a discussion of the methods of evangelization and the firm resistance of the Indian population, which climaxed in the general uprising of 1709.